2-(6-Methoxynaphthalen-2-yl)-1-(morpholin-4-yl)propan-1-one - Nasirullah (International Union of Crystallography, 2012)
In the title compound, C(18)H(21)NO(3), the naphthalene group and the basal plane of the morpholine ring (r.m.s. deviations = 0.0177 and 0.0069 Å, respectively) are oriented at a dihedral angle of 44.0 (2)°. In the crystal, molecules are linked by C—H⋯π interactions.